Perancangan Program Aplikasi Sistem Informasi Akuntansi Penjualan Tunai dengan menggunakan Microsoft Access 2016: (Studi Kasus pada Toko Beras Barokah) - Men, Chen Qiu; Afriady, Arif (Indonesian Accounting Literacy Journal, 2025)
In this era of globalization, the development of information technology is very influential in various fields, including in the field of sales. Toko Beras Barokah is a rice shop that has been around for 5 years with a daily turnover of IDR 4,000,000 to IDR 6,000,000. Until now, the Toko Beras Barokah has recorded sales manually, so that problems arise such as recording sales that are not in accordance with the amount of income received. This study aims to determine the cash sales procedure at the Toko Beras Barokah, to design a cash sales application program at the Toko Beras Barokah, and to implement an accounting information system for cash sales at the Toko Beras Barokah using qualitative research methods and using theanalysis tool System Development Life Cycle. With this sales recording application, it is hoped that it can help micro-enterprises in recording their sales transactions efficiently, quickly, and accurately. The output of this sales accounting information system application is sales reports and product inventory reports, and can display sales charts based on product codes.